The Effectiveness of Youtube as a Platform for Islamic Da’wah and Counseling for Generation Z in the Digital Era - Maesa Ayu Rohmatus Sa’diah, Maesa; Alyawanda Aqlinna Hanif (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
This study aims to examine the effectiveness of YouTube as a platform for Islamic preaching and counseling for Generation Z in the digital era. Using a literature study approach, this research analyzes various relevant sources, including books, scientific journals, and articles obtained from the internet. The findings show that YouTube is effective as a medium for Islamic preaching and counseling for Generation Z in the digital era. The platform can deliver messages in an engaging, easy-to-understand manner and align with the characteristics of Generation Z, who are closely connected to interactive visual content. Proper utilization of YouTube can enhance audience engagement and support the achievement of Islamic preaching and counseling objectives. This study recommends the development of creative and innovative content based on the needs of Generation Z to make preaching and counseling more relevant and optimal.